Analysis of ICT Infrastructure and Tourism Informational Needs: A Case Study of Nepal (International Journal of Innovative Research in Computer Science & Technology, 2021)
Tourism finds enormous application of ICT  in the development of strategic and operational goals. ICT  promises long-term benefits and is a leading force in the  tourism industry to enhance development and economic  growth. The tourism industry in the western world and  some developed countries of Asia have applied ICT for  more than 30 years, and have gained tremendous benefits.  Nepal which is also growing as one of the favorite tourist  destinations lacks proper implementation of ICT in this  sector. In our study, we examined how ICT can play a vital  role in developing the tourism industry of Nepal. This study  is exploratory research based on primary data collected  from tourists visiting Nepal, supported by information from  tour operators, government agencies, NGOs, and INGOs. A  framework is devised based on data and information  collected and finally, discussions elaborate on the  informational needs, technological architecture, and  challenges for the implementation of ICT in the tourism  industry of Nepal.
Keywords: ICT; Tourism governance; Tourism business; Technology development; Nepal